Gametofitos y esporofitos jóvenes de Dryopteris wallichiana (Spreng.) Hyl. (Dryopteridaceae - Pteridophyta) - Narváez, Paula Liliana; Martínez, Olga Gladys; Sota, Elías Ramón De La (Botanica Complutensis, 2008)
Morphogenesis of the Dryopteris wallichiana (Spreng.) Hyl. gametophytes and morphology of young sporphytes are presented on the basis of in vitro culture. The germination pattern is Vittaria-type, prothallial development corresponds to Aspidium-type. The laminar prothalli are cordated and spatulated. The mature prothalli only originate antheridia of the common type for leptosporangiate ferns. The spatulated gametophytes develop a larger quantity of antheridia. It is an obligated apomictic species. The sporophytes are originated from cordated prothalli. The first laminae are trilobate, then they divide into pinnated plan. They have unicellular and pluricellular trichomes on the margin and both sides of the lamina.
Keywords: Morphogenesis; Dryopteris wallichiana; Prothalli; Obligate apogamy